Influence of harvest method on proximate composition, texture profile and protein oxidation of beef from grain-fed Nellore cattle - Salim, Ana Paula Amaral de Alcântara; Suman , Surendranath; Viana, Fernanda Medeiros; Canto, Anna Carolina Vilhena da Cruz Silva; Monteiro, Maria Lucia Guerra; Conte-Junior , Carlos Adam; Mano, Sérgio Borges (Acta Scientiarum. Animal Sciences, 2023)
The influence of harvest method on proximate composition, protein oxidation, and texture profile of beef from Nellore cattle were investigated. Longissimus lumborum (LL) muscles were obtained from twelve grain-fed Nellore carcasses. The animals were slaughtered after stunning (STU; n=6) or without stunning (WST; n=6) and after 24 hours postmortem, the LL was sliced into 2.54-cm steaks, packed under aerobic conditions, and stored at 4°C for nine days. Proximate composition was analyzed on day 0, whereas protein oxidation (carbonyl content) and texture profile (hardness, chewiness, cohesiveness, and springiness) were evaluated on days 0, 3, 6, and 9. STU and WST steaks exhibited similar proximate composition, hardness, and chewiness (p > 0.05). WST steaks exhibited greater protein oxidation and lower cohesiveness than their STU counterparts on day 0 (p < 0.05). Concerning the storage period, WST steaks demonstrated a decrease in springiness and a more pronounced increase in cohesiveness than their STU counterparts (p < 0.05). These results indicated that the harvest method influenced LL protein oxidation and texture profile from Bos indicus cattle.